Digital Accessibility Management For Students In an Inclusive School: A Case Study in Indonesia - Maysaroh, Anisatul; Sukirman, Sukirman; Hidayati, Dian (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Inclusive education in Indonesia still faces challenges in ensuring adequate digital accessibility for students with special needs. This study aims to identify digital accessibility management strategies in inclusive schools using the Planning, Organizing, Actuating, Controlling (POAC) management approach. The research was conducted at SD Al-Irsyad Al-Islamiyyah Jember using qualitative methods through semi-structured interviews and document analysis, which was processed with ATLAS.ti 9 software. The results showed that planning includes analyzing students' needs, organizing a special team, implementing digital training for teachers and students, and evaluation through student progress reports and regular meetings with parents. The findings reveal that the application of digital technology increases students' independence and motivation, although it still faces obstacles such as limited resources. This study recommends continuous training and policy support to strengthen digital accessibility in inclusive schools.